2013
DOI: 10.15282/ijame.8.2013.6.0094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper and Magnesium on Phase Formation Modeling and Mechanical Behavior in AL-CU-MG Alloys

Abstract: The current work emphasizes the establishment of a relationship between microstructure, and copper and magnesium addition in aluminum based alloys. Aluminum alloys containing 4 and 6% copper and 0.50 and 1% magnesium were cast from commercially pure aluminum ingots and homogenized at 400 o C. Images of the microstructures of the as-cast and homogenized alloys were acquired, and image analysis of the phases was performed on the acquired images to obtain area fractions of the phases present in the microstructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…After the tensile and impact tests, the fractured specimens were cleaned and polished for microscopic observation of the fracture surface. The impact of dynamic loading on the microstructure and mechanical properties of a Cu-Zn alloy at liquid nitrogen temperature (77 K) with different strains was studied and it was found after the tensile test that during dynamic loading brass showed a high strength and limited ductility [21,22]. Figure 4 shows the microstructure of the fracture surface after the tensile testing of E-Cu and pure copper alloys.…”
Section: Microstructurementioning
confidence: 99%
“…After the tensile and impact tests, the fractured specimens were cleaned and polished for microscopic observation of the fracture surface. The impact of dynamic loading on the microstructure and mechanical properties of a Cu-Zn alloy at liquid nitrogen temperature (77 K) with different strains was studied and it was found after the tensile test that during dynamic loading brass showed a high strength and limited ductility [21,22]. Figure 4 shows the microstructure of the fracture surface after the tensile testing of E-Cu and pure copper alloys.…”
Section: Microstructurementioning
confidence: 99%
“…The magnesium alloy is characterized as a lightweight material and has high energy absorption capability. Magnesium alloys can naturally withstand impacts effectively because of their unique combination of high tensile strength, low density, and superior shock absorbency which are 100 times greater than that of ordinary aluminum alloys [5,8,9]. Split Hopkinson Pressure Bar (SHPB) was modernized by Herbert Kolsky in 1949 [10,11] and is applicable to high velocity impact for high strain rate testing [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical and electrical properties of the Cu-Ag alloys have been studied during cold working operations and it was found that by adding a percentage of Cr, tensile strength increases whereas electrical conductivity decreases [9]. A research investigated the microstructural behaviour and mechanical properties of copper and brass alloys by the tensile and impact tests and found that during dynamic loading, brass showed a high strength with reduced ductility [10].…”
Section: Introductionmentioning
confidence: 99%